Implementation of Authentic Assessment Through Dice Games to Measure Early Childhood Cognitive Development at Nur Faizah PAUD, Bingin Rupit Village - Yeni, Nini Angger; Alfauzan Amin (PT Inovasi Pratama Internasional, 2026)
Early childhood development assessment needs to be conducted authentically and enjoyably, in accordance with the characteristics of learning through play. However, assessment practices in early childhood education (PAUD) are still dominated by traditional assessments that do not reflect children's natural abilities. This study examines the use of dice games as a medium for assessing children's cognitive development at Nur Faizah PAUD to overcome the limitations of conventional assessments and improve the accuracy of learning assessments. The study aims to describe the implementation of dice-based assessments and their effectiveness in assessing numeracy and number recognition skills. This study used a qualitative descriptive approach through observation, interviews, and documentation of 15 children in group B and their classroom teachers. The results showed that dice games can increase learning motivation and enable cognitive assessment to occur naturally. Most children were able to correctly name the numbers according to the dice roll results, and approximately 70% of children were able to perform simple addition using two dice. In addition to academic outcomes, this activity also stimulated social-emotional development such as cooperation, waiting for turns, emotional regulation, and communication during play. Teachers acknowledged that assessment through dice games facilitated observation of the learning process without causing stress for children, although obstacles such as limited game equipment and recording of assessment results were still encountered. Overall, the dice game proved to be an effective, fun, and developmentally appropriate assessment instrument for early childhood, and supported the principles of the Independent Curriculum, which is oriented towards meaningful and child-centered learning.